Experimental study on the bubble breakage in a stirred tank. Part 1. Mechanism and effect of operating parameters. (December 2017) - Hasan, Basim O.
Highlights: The mechanism of single bubble breakage in the agitated tank was deeply investigated using high speed imaging method. The effect of agitation speed and mother bubble size on the breakage characterization parameters was investigated. The breakage probability, breakage time, and the number of daughter bubbles were determined and discussed. The dynamic behavior of a bubble starting from its beginning deformation until the last breakage event was analyzed and discussed. Abstract: An experimental study on single bubble breakage in a stirred tank with 4 baffles using a Rushton turbine impeller that had six blades was carried out. The experiments were performed for agitation speeds between 220 rpm and 420 rpm and for mother bubble diameters (dp ) between 2.2 mm and 4.0 mm. The motion of a single bubble injected into the impeller region of high energy dissipation rate was followed using a high speed camera to gain a deeper insight of the breakage mechanism and bubble dynamic. Important conclusions regarding the mechanisms of breakage and the effect of operating parameters on breakage characteristics were identified. The dynamic behavior of a bubble starting from its beginning deformation until the last breakage event was analyzed and discussed. Qualitative and quantitative results were obtained for the effect of Reynolds number ( Re ) and mother bubble size on the breakage probability, breakage time, number of daughter bubbles and the sizes of the daughter bubbles. The results revealed that the mechanisms governing the breakage are mainly related to turbulence intensity and shear forces that are exerted on the mother bubble by continuous phase and by the impeller blade. Depending on the turbulence level, the mother bubble experienced different deformation scales prior to the breakage such as necking, stretching, elongation, threading, and highly irregular shapes which influenced the number of produced fragments. The breakage probability was found to be an increasing function of power input (or agitation speed) and mother bubble size. The probability of binary breakage and equal sized breakage were found to be small and to decrease with increasing power input and mother bubble size. The initial breakage time exhibited an increasing trend with power input but an unstable trend with mother bubble size. The duration of the time interval between first breakage event and last breakage was found to increase with Re and mother bubble size. This interval became longer and included a significant amount of successive breakages especially when the bubble was caught by eddies close to the blade.